Counting one's blessings : the selected letters of Queen Elizabeth the Queen Mother - Elizabeth, Queen, consort of George VI, King of Great Britain, 1900-2002 (Farrar Straus and Giroux, 2012)
William Shawcross's official biography of Queen Elizabeth the Queen Mother, published in September 2009, was a huge critical and commercial success. One of the great revelations of the book was Queen Elizabeth's insightful, witty private correspondence. Indeed, The Sunday Times described her letters as "wonderful ... brimful of liveliness and irreverence, steeliness and sweetness." Now, Shawcross has put together a selection of her letters, drawing on the vast wealth of material in the Royal Archives and at Glamis Castle. Queen Elizabeth was a prolific correspondent from her earliest childhood before the First World War to the very end of her long life at the beginning of the twenty-first century, and her letters offer readers a vivid insight into the real person behind the public face.--From publisher description.